Confirmatory Factor Analysis of the Academic Self-Efficacy Scale: An Indonesian Version - Kusumasari Kartika Hima Darmayanti; Erlina Anggraini; Efan Yudha Winata; M. Fariz Fadillah Mardianto (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2021)
Several studies regarding academic self-efficacy are developed in which a valid and reliable measurement is needed. One of the well-known instruments used to measure college students' academic self-efficacy is The Academic Self-Efficacy Scale (TASES). It was designed by Sagone and Caroli (2014), comprising four dimensions, i.e., self-engagement, self-oriented decision-making, others-oriented problem-solving, and interpersonal climate. This instrument contained 30 items at first, but two items were removed after testing the factor analysis, and 28 items remained. This study examined the validity of the adaptation of TASES into the Indonesian version. This scale was adapted into the Indonesian version using confirmatory factor analysis (CFA), involving 166 Indonesian college students studying at universities in Indonesia and abroad. The CFA results showed that the items which were distributed in 4 dimensions in this scale are found to fit except three items of interpersonal climate dimension. Therefore those three items have been eliminated. In addition, the coefficient of Cronbach's Alpha of TASES Indonesian version is highly reliable. Ultimately, the TASES Indonesian version consisting of 25-item within four dimensions has shown to be a reliable and valid measurement for academic self-efficacy in the Indonesian context.